ANALISIS KESALAHAN KALIMAT BAHASA INDONESIA PADA BERITA TRIBUN-TIMUR.COM - Meirsanda, Rani; Hamsa, Akmal; Usman (Journal of Applied Linguistics and Literature, 2024)
This research is a qualitative research that aims to describe Indonesian sentence pattern errors, Indonesian diction errors in online media news Tribun-Timur.com. The data in the research are news sentences containing Indonesian sentence pattern errors and Indonesian diction errors. The data source of this research is news published by Tribun-Timur.com online media published in its portal in the period August to November 2023. The results of this study show that: Indonesian sentence pattern errors on Tribun-Timur.com news, including Subject Errors, namely subject errors that do not match the number, wrong word selection, grammatical conformity errors; Predicate Errors in Tribun-Timur. Object Errors, which are discrepancies between the subject and predicate in a sentence; Object Errors, which are discrepancies in the type of nouns, discrepancies in the number of nouns, discrepancies in the use of object pronouns, and discrepancies in prepositions; Description Errors, which are discrepancies in time, discrepancies in place, discrepancies in manner, discrepancies in intensity level, and discrepancies in order; Complementary errors, namely mismatch of complement type, mismatch of complement number, mismatch of conjunction, mismatch of complement meaning, and mismatch of complement phrase; and Indonesian diction errors on Tribun-Timur. com news, namely the use of words that are not in accordance with the value of taste, the use of words through language styles that create nuances of negative ideas, and the use of words that cause ambiguity.